Core-collapse, evaporation, and tidal effects: the life story of a self-interacting dark matter subhalo. Issue 4 (25th April 2022) - Zeng, Zhichao Carton; Peter, Annika H G; Du, Xiaolong; Benson, Andrew; Kim, Stacy; Jiang, Fangzhou; Cyr-Racine, Francis-Yan; Vogelsberger, Mark
ABSTRACT: Self-interacting dark matter (SIDM) cosmologies admit an enormous diversity of dark matter (DM) halo density profiles, from low-density cores to high-density core-collapsed cusps. The possibility of the growth of high central density in low-mass haloes, accelerated if haloes are subhaloes of larger systems, has intriguing consequences for small-halo searches with substructure lensing. However, following the evolution of 10^8 M_ subhaloes in lens-mass systems (10^13 M_ ) is computationally expensive with traditional N -body simulations. In this work, we develop a new hybrid semi-analytical + N -body method to study the evolution of SIDM subhaloes with high fidelity, from core formation to core-collapse, in staged simulations. Our method works best for small subhaloes (≲1/1000 host mass), for which the error caused by dynamical friction is minimal. We are able to capture the evaporation of subhalo particles by interactions with host halo particles, an effect that has not yet been fully explored in the context of subhalo core-collapse. We find three main processes drive subhalo evolution: subhalo internal heat outflow, host-subhalo evaporation, and tidal effects. The subhalo central density grows only when the heat outflow outweighs the energy gain from evaporation and tidal heating. Thus, evaporation delays or even disrupts subhalo core-collapse. We map out the parameter space for subhaloes to core-collapse, finding that it is nearly impossible to drive core-collapse in subhaloes in SIDM models with constant cross-sections. Any discovery of ultracompact dark substructures with future substructure lensing observations favours additional degrees of freedom, such as velocity-dependence, in the cross-section.